Enhancing the Efficiency of International Trade: Exploring the Impact of Blockchain Technology on Letter of Credit within Existing Legal Frameworks - Aminizadeh, Laya (Debreceni Jogi Műhely, 2024)
A letter of credit is a crucial document widely employed in international trade, primarily for payment purposes, and consequently imposes rights and responsibilities on the involved parties. The payment and fulfillment of obligations are among the most significant aspects in any contract. Among the payment methods in international transactions, the letter of credit is the most reliable and significant method due to its distinctive characteristics. Through the involvement of banks, a letter of credit ensures the secure guarantee of interests for both the seller and the buyer, alleviating their concerns. However, in light of advancements in international trade, it becomes essential to consider the impact of emerging technologies on payment methods in international business relationships. This commentary aims to investigate recent research on the utilization of Blockchain-based letters of credit, offering a comprehensive perspective on regulatory frameworks within this domain.After a detailed description of Blockchain structure for letter of credit and examining the use cases of Smart LCs, the research suggests that existing legal frameworks, such as the UCP, eUCP, ISP98, and UN LC convention, can serve as a basis for managing Blockchain-based LCs with necessary amendments. By integrating Blockchain technology and leveraging these frameworks, trade finance can benefit from increased efficiency, transparency, and security.